Highly replicated sampling reveals no diurnal vertical migration but stable species-specific vertical habitats in planktonic foraminifera. (25th February 2019) - Meilland, Julie; Siccha, Michael; Weinkauf, Manuel F G; Jonkers, Lukas; Morard, Raphael; Baranowski, Ulrike; Baumeister, Adrian; Bertlich, Jacqueline; Brummer, Geert-Jan; Debray, Paul; Fritz-Endres, Theresa; Groeneveld, Jeroen; et al.
Abstract: Diurnal vertical migration (DVM) is a widespread phenomenon in the upper ocean, but it remains unclear to what degree it also involves passively transported micro- and meso-zooplankton. These organisms are difficult to monitor by in situ sensing and observations from discrete samples are often inconclusive. Prime examples of such ambiguity are planktonic foraminifera, where contradictory evidence for DVM continues to cast doubt on the stability of species vertical habitats, which introduces uncertainties in geochemical proxy interpretation. To provide a robust answer, we carried out highly replicated randomized sampling with 41 vertically resolved plankton net hauls taken within 26 hours in a confined area of 400 km 2 in the tropical North Atlantic, where DVM in larger plankton occurs. Manual enumeration of planktonic foraminifera cell density consistently reveals the highest total cell concentrations in the surface mixed layer (top 50 m) and analysis of cell density in seven individual species representing different shell sizes, life strategies and presumed depth habitats reveals consistent vertical habitats not changing over the 26 hours sampling period. These observations robustly reject the existence of DVM in planktonic foraminifera in a setting where DVM occurs in other organisms.